Optical properties of phenanthrene: A DFT study for comparison between linear and nonlinear regimes. (May 2016) - Omidi, A.R.; Dadsetani, M.
Abstract: The present study tries to determine the optical characteristics as well as the electronic structure of phenanthrene as an important nonlinear organic crystal. We have performed our calculations within the frame work of DFT. Also, we have used bootstrap exchange-correlation kernel (within the framework of TDDFT) to estimate the excitonic effects. According to the results of our study, the investigated crystal has a band structure with low dispersions which is a sign of low intermolecular interactions. In addition to the high values of linear and nonlinear susceptibilities, the crystal in question has a wide range of transparency as well as sufficient anisotropy which make it promising crystal for nonlinear optical applications. Our TDDFT calculations show that the influence of excitonic effects on optical properties can be very dramatic, particularly near the band edge. In addition, the crystal in question shows extremely small wavelengths of plasmon peaks. Furthermore, this study also covers the 2 ω / ω intra- and inter-band contributions to the dominant nonlinear susceptibilities. Findings indicate that these contributions have opposite signs at higher energies and nullify each other. Our calculations show that χ x x z, χ x z x and χ z x x have largest values of nonlinear response but χ x x z is the dominant component at IR-VIS region. Moreover, the current study shows significant similarities between linear and nonlinear spectra, when we draw linear one as a function of both ω and 2 ω . Finally, our simulation reproduces the experimental results very well. Highlights: The band structure of investigated crystal shows low dispersions, due to the low intermolecular interactions. The investigated crystal has large anisotropy, especially below the band gap. Phenanthrene has high values of nonlinear susceptibility, especially in the visible and near ultraviolet regions. Excitons can play major roles, especially near the band edge. Phenanthrene is an organic crystal with extremely small wavelengths of Plasmon peaks.